The strength growth rhythms in Ecuadorian children from 6 to 12 years old, male and female gender/Los ritmos de crecimiento de la fuerza en niños ecuatorianos de 6-12 años, sexo masculino y femenino - Paul Isaías Marcillo Iza; Jorge Washington Tipán Gualotuña; Edgardo Romero Frómeta (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2022)
For the selection of probable sports talents, several determination procedures have been presented with indicators, based on physical capacities, including strength. Strength makes it possible to oppose endurance by means of muscular tension. This is a physical capacity, the basis of sports performance, so it is useful to establish its evolution in the stages of sports initiation from a specialized methodological perspective. Therefore, the purpose of the research is to determine the dynamics of the growth times of the strength capacity, in the age group between 6-12 years old in both genders. A descriptive-analytical type of research is used, three strength determination tests are applied (jump without impulse running, 30s abdominals and 30s elbow flexion) to a representative sample of 412 girls and 633 boys between 6-12 years of age from the 24 provinces of Ecuador, determining the growth rates of the physical capacity of strength in Ecuadorian children in the mentioned age range, both genders.